(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
The absence of agreement among scholars regarding the halal consumption of jallālah animals necessitates an investigation of the basic text of the hadith which is used to examine the extent of the position of the hadith text so that it can be used as a basis. The purpose of the study is to trace the text of the hadith, its purification, and to describe the laws that it produces. The research method uses qualitative methods with a literature review approach. The data source is in the form of publication of hadith history which contains a prohibition on consuming Jallālah. The data analysis technique used takhrij al-ḥadith followed by sharḥ al-ḥadith. This article finds that there is a qualified history regarding the prohibition of consuming jallalah. The law contained in the prohibition is makruh